Cultivating public service competencies in student employees: a case study. Issue 3 (3rd July 2021) - Harrington, Sarah; Lewis, Nancy; Brown, Nicole E.
Abstract: How can we best train student employees for public service roles? At UC Berkeley, as in many academic libraries, a student employee is the first person that a user will see when entering the library; they are the "face of the library." A positive interaction will set a positive tone for the user's library experience, while a negative interaction may discourage the user from ever visiting the library again. As such, it is critical to prepare student staff with the competencies to engage positively with library users and feel confident in their roles. This paper shares a case study of a public services training piloted for Access Services student employees at UC Berkeley.